Islamic Law Review of Marriages of Pregnant Women Out of Marriage and the Status of Their Children - Gunawan; Sainun; Gazali (al-Afkar, Journal For Islamic Studies, 2025)
In the era of science and technology, the use of social media can hardly be limited because it crosses space, time and place, so that the Islamic ummah is increasingly faced with various problems, both those that directly touch Islamic teachings and other problems that still have something to do with Islam and these problems require a solution instrument and one of these instruments is Islamic law. One of the problems that is currently widespread is promiscuity among young people who not only meet in person but have spread to social media such as FB, WA, Instagram and so on which makes meeting easier, so that many things appear that should not happen to the Islamic generation, for example, dating relationships and even premarital sex which causes pregnancies outside of marriage whose impact is not good for individuals and society, so that it becomes material for gossip because marriage is caused by pregnancy outside of marriage and the problem does not stop there and even continues to the status of the child who was born.